Early Reading Ability Assessment Instrument for Children Aged 5-6 Years in the Context of Early Childhood Education - Mulyawati Zulfadhliyah; Shofia Hartati; Hapidin Hapidin (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
The use of assessment instruments that have not been tested for validity can lead to inaccurate assessments of the early reading abilities of 5-6 year old children and result in inappropriate learning stimulation. This study aims to analyze the validity and reliability of instruments for assessing the early reading abilities of 5-6 year old children. The method used was Research and Research (R&R) with preliminary research, instrument development, and effectiveness testing stages, involving two kindergarten teachers as subjects and assessment instruments as research objects. The data collection instrument. was a non-test questionnaire used to assess the instrument's suitability. The data were analyzed using quantitative descriptive statistical analysis. The results showed a validity value of 0.2960 and a reliability value of 0.780, indicating that the instrument was valid and reliable. These findings imply the availability of an early reading assessment instrument that is suitable for use in supporting objective assessment and the development of early literacy in young children.